Impact of non-emergency surgical timing on postoperative recovery quality in mild or asymptomatic SARS-CoV-2 infected patients: a grouped cohort study - Qiu-Bo Wang; Yu-Long Wang; Yue-Feng Wang; Hua Chen; Wei Chen; Yong-Quan Chen (BMC Anesthesiology, 2024)
Abstract Objective To explore the relationship between the timing of non-emergency surgery in mild or asymptomatic SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) infected individuals and the quality of postoperative recovery from the time of confirmed infection to the day of surgery. Methods We retrospectively reviewed the medical records of 300 cases of mild or asymptomatic SARS-CoV-2 infected patients undergoing elective general anaesthesia surgery at Yijishan Hospital between January 9, 2023, and February 17, 2023. Based on the time from confirmed SARS-CoV-2 infection to the day of surgery, patients were divided into four groups: ≤2 weeks (Group A), 2–4 weeks (Group B), 4–6 weeks (Group C), and 6–8 weeks (Group D). The primary outcome measures included the Quality of Recovery-15 (QoR-15) scale scores at 3 days, 3 months, and 6 months postoperatively. Secondary outcome measures included postoperative mortality, ICU admission, pulmonary complications, postoperative length of hospital stay, extubation time, and time to leave the PACU. Results Concerning the primary outcome measures, the QoR-15 scores at 3 days postoperatively in Group A were significantly lower compared to the other three groups (P < 0.05), while there were no statistically significant differences among the other three groups (P > 0.05). The QoR-15 scores at 3 and 6 months postoperatively showed no statistically significant differences among the four groups (P > 0.05). In terms of secondary outcome measures, Group A had a significantly prolonged hospital stay compared to the other three groups (P < 0.05), while other outcome measures showed no statistically significant differences (P > 0.05). Conclusion The timing of surgery in mild or asymptomatic SARS-CoV-2 infected patients does not affect long-term recovery quality but does impact short-term recovery quality, especially for elective general anaesthesia surgeries within 2 weeks of confirmed infection. Therefore, it is recommended to wait for a surgical timing of at least greater than 2 weeks to improve short-term recovery quality and enhance patient prognosis.